Character Building Of The Young Generation Through Pencak Silat Tapak Suci Putera Muhammadiyah - M. Amar Ma’ruf; Hadi Pajarianto; Rasyidah Jalil (JUARA : Jurnal Olahraga, 2022)
Pencak silat is the nation's cultural heritage that has been passed down for thousands of years, maintained and passed down from generation to generation. Apart from being a sport of self-defence and achievement, Pencak silat is also a way to build the character of the younger generation. The purpose of this research; is (a) to identify the fundamental values ​​of Pencak silat tapak suci; (b) to find the dominant character values ​​in the Pencak silat tapak suci, and (c) to explore coaching strategies in the Pencak Silat Tapak Suci. The method used is qualitative by involving 30 informants of Tapak Suci cadres. Data collection by interview and analysis is done through ongoing research with the interactive model and analysis techniques, including data reduction, data presentation, and conclusions or verification. The results showed that the fundamental values ​​of the Tapak Suci are a brotherhood that comes from the Qur'an and Sunnah and stays away from shirk. At the same time, the dominant character values ​​are discipline, tolerance, hard work, religion, and love of peace. While the pattern of coaching by strengthening Al-Islam, kemuhammadiyahan, and organizational knowledge. The conclusion of this research is that Pencak Silat is an effective instrument to improve the character of the young generation and to preserve the nation's culture.